Evaluation of the Differential Postbiotic Potential of Shewanella putrefaciens Pdp11 Cultured in Several Growing Conditions - Domínguez-Maqueda, Marta; Tapia-Paniagua, Silvana Teresa; González-Fernández, Carmen; Cuesta, Alberto; Espinosa-Ruiz, Cristóbal; Esteban, María Ángeles; Alarcón, Francisco Javier; Balebona-Accino, María del Carmen; Moriñigo-Gutiérrez, Miguel Ángel (Springer Nature, 2023)
The increased knowledge of functional foods has led to the development of a new generation of health products, including those containing probiotics and products derived from them. Shewanella putrefaciens Pdp11 (SpPdp11) is a strain described as a probiotic that exerts important beneficial effects on several farmed fish. However, the use of live probiotic cells in aqua‑culture has limitations such as uncertain survival and shelf life, which can limit their efficacy. In addition, its efficacy can vary across species and hosts. When probiotics are administered orally, their activity can be affected by the environment present in the host and by interactions with the intestinal microbiota. Furthermore, live cells can also produce undesired substances that may negatively impact the host as well as the risk of potential virulence reversion acquired such as antibiotic resistance. Therefore, new alternatives emerged such as postbiotics. Currently, there is no knowledge about the postbiotic potential of SpPdp11 in the aquaculture industry. Postbiotic refers to the use of bacterial metabolites, including extracellular products (ECPs), to improve host physiology.
Keywords: Microbiología; Shewanella putrefaciens Pdp11; Postbiotic; Extracellular products; Growing conditions